Currículo integrado : uma reflexão entre o legal e o real - Estivalete, Emerson Bianchini (2014)
The present work is a reflection about the integrated curriculum, its legal propositions and possibilities of practical implementation in the context of a technical course. For this qualitative investigation, the case study within the ethnographic research was selected. The field research was the oral reports of two groups of subjects belonging to the same institution, making a total of 14 participants. The first group was formed by teachers and educational technicians and the second group by students enrolled in the third year of the agriculture technical course integrated to secondary school and maintained by the Federal Institute of Education, Science and Technology of Santa Catarina Campus Rio do Sul. The data collection occured from August 2012 to October 2013 and was done through participant observation, documentary analysis and semistructured interviews. Data was analysed through Textual Discursive Analysis according to Galiazzi & Moraes (2007) and resulted in the following categories: Group A: interdisciplinary perspectives; articulation theory - practice, facing the challenges of teaching. Group Two: youth and schooling; integration of knowledge; life project and future. The research findings suggest that legal propositions related to the investigated course did not cause major changes due to the conservation of relations with capitalist system that has strongly influenced the construction of curricula of technical courses. Although the professionals involved in this research recognize the importance of integrating knowledge across the curriculum, only specific attitudes through some curriculum components or the performance of few interdisciplinary projects were identified until the end of this investigation. This study can contribute to reflections about the possibilities for building effective interdisciplinary attitudes that may be sensitive to collective demands in which the meaning of learning gain greater projection for everybody involved in the educational processes.